2017
DOI: 10.3389/fpsyg.2017.00041
|View full text |Cite
|
Sign up to set email alerts
|

Tears Falling on Goosebumps: Co-occurrence of Emotional Lacrimation and Emotional Piloerection Indicates a Psychophysiological Climax in Emotional Arousal

Abstract: This psychophysiological study is the first to examine the relationship between emotional tears and emotional piloerection (i.e., goosebumps). Although both phenomena have been related to peak states of being moved, details about their temporal occurrence and the associated levels of physiological arousal have remained unknown. In our study, we used emotionally powerful film scenes that were self-selected by participants. Our findings show that even within peak moments of emotional arousal, a gradation of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 74 publications
(151 reference statements)
12
104
1
1
Order By: Relevance
“…Among those clues is the sensation of "chills" (also seen in literature as "shivers, " "frisson, " "tingles"), and often their concurrence with visual piloerection, or commonly known as goose bumps ("goose flesh") (Keltner and Haidt, 2003;Grewe et al, 2009;Benedek and Kaernbach, 2011;Nusbaum and Silvia, 2011;Stellar et al, 2017). Among the studies by Benedek and Kaernbach (2011), Quesnel and Riecke (2017), Sumpf et al (2015), and Wassiliwizky et al (2017), there is overall a 40% rate of goose bump elicitation in participants who watched moving/awe-inspiring videos or VR as stimuli. The consistency of this rate means goose bumps (with concurring chills or not) may be experienced by some people but not others, or that lab-induced stimuli may elicit less-intense awe experiences, theorized by Benedek and Kaernbach (2011), Silvia (2012), and Silvia et al (2015).…”
Section: Experiential Components and Outcomes Of Overview Effectmentioning
confidence: 99%
“…Among those clues is the sensation of "chills" (also seen in literature as "shivers, " "frisson, " "tingles"), and often their concurrence with visual piloerection, or commonly known as goose bumps ("goose flesh") (Keltner and Haidt, 2003;Grewe et al, 2009;Benedek and Kaernbach, 2011;Nusbaum and Silvia, 2011;Stellar et al, 2017). Among the studies by Benedek and Kaernbach (2011), Quesnel and Riecke (2017), Sumpf et al (2015), and Wassiliwizky et al (2017), there is overall a 40% rate of goose bump elicitation in participants who watched moving/awe-inspiring videos or VR as stimuli. The consistency of this rate means goose bumps (with concurring chills or not) may be experienced by some people but not others, or that lab-induced stimuli may elicit less-intense awe experiences, theorized by Benedek and Kaernbach (2011), Silvia (2012), and Silvia et al (2015).…”
Section: Experiential Components and Outcomes Of Overview Effectmentioning
confidence: 99%
“…Most recently, other researchers have focused on the physiology of the combination of tears and chills (goosebumps), both characteristic expressions of being moved, in response to participant-selected film clips [33,34]. Specifically, Wassiliwizky et al [33] observed increased sympathetic activity (e.g., increased skin conductance and heart rate) in periods of tearful crying, which always followed rather than preceded goosebumps. Mori and Iwagana [34] also showed that chills and tears developed during emotional music that elicited increases in arousal.…”
Section: Crying and The Autonomic Nervous Systemmentioning
confidence: 99%
“…Research assessing moving or touching experiences has been conducted using U.S. American (Schubert, Zickfeld, Seibt, & Fiske, 2016;Thomson & Siegel, 2013), British (Schnall & Roper, 2012;Schnall et al, 2010), French-speaking Swiss (Cova & Deonna, 2014), German (Kuehnast et al, 2014;Menninghaus et al, 2015;Wassiliwizky, Jacobsen, Heinrich, Schneiderbauer, & Menninghaus, 2017), Japanese (Tokaji, 2003), Dutch (Strick et al, 2015), Norwegian (Seibt, Schubert, Zickfeld, & Fiske, 2017), and Finish (Vuoskoski & Eerola, 2017) participants. Yet each of these studies has used different elicitors and different methods, so, to date no study has systematically compared responses to moving stimuli with the same measures across a range of cultures.…”
Section: Being Moved: Phenomenology Elicitors and Outcomesmentioning
confidence: 99%